2009
DOI: 10.1021/jp903519c
|View full text |Cite
|
Sign up to set email alerts
|

An Accurate Equation of State for Fluids and Solids

Abstract: A simple functional form for a general equation of state based on an effective near-neighbor pair interaction of an extended Lennard-Jones (12,6,3) type is given and tested against experimental data for a wide variety of fluids and solids. Computer simulation results for ionic liquids are used for further evaluation. For fluids, there appears to be no upper density limitation on the equation of state. The lower density limit for isotherms near the critical temperature is the critical density. The equation of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…Following the notation used by Parsafar et al [40,44], the configurational energy and the exact thermodynamic EoS using the new model for the solid systems have been obtained in good agreement with the experimental data.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Following the notation used by Parsafar et al [40,44], the configurational energy and the exact thermodynamic EoS using the new model for the solid systems have been obtained in good agreement with the experimental data.…”
Section: Discussionsupporting
confidence: 64%
“…In the other words, the parameter β corrects the difference between the two-body results and the experimental data. In order to obtain the equation of state for the solid systems, we have used the theory developed by Parsafar et al [40].…”
Section: Interaction Potentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the phase behavior of solid bulk neon has been the subject of many experimental and theoretical investigations, but there is no much known about the neon In this work, the NVT-MD simulations have been used to calculate the densities of neon nanoclusters using new corrected potential for the temperatures from 2 to 12 K and pressures from 0.1 to 1 GPa. We have then tted the simulated results to the EoS of Parsafar et al 23 and developed its parameters as functions of temperature and particles size. This EoS gives a good description for all types of uid, including nonpolar, polar, hydrogen-bonded, and metallic, for temperatures ranging from the triple point to the highest temperature for which experimental data are reported.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the effective interactions of an extended Lennard-Jones (12, 6, 3) type, Parsafar et al 23 showed that for a wide variety of uids and solids, the average congurational energy per particle can be given by:…”
Section: Intermolecular Potentialsmentioning
confidence: 99%